Enhancing RCPsych Addiction Competencies: A Pilot Programme Integrating Training and Taster Days for North London Foundation Trust’s Core Trainees - Munzir Quraishy; Harrison Howarth; Chern Wong; Yathooshan Ramesh; Kevin O’Neill (BJPsych Open, 2025)
Aims: There are new requirements for addictions competencies as part of the 2022 core trainee curriculum. The Silver Guide, section 5.1.2 includes a requirement for two work based placed assessments (WBPA) in addictions to be completed during core training. This has posed challenges nationally, especially in England due to the way addiction services are commissioned and tendered. Whilst most training schemes have opted for CBD groups, our region of London wanted to provide practical and experiential learning with taster days at both NHS and 3rd sector services. Trainees were an integral part of the stakeholder group to ensure co-production.